Transconjunctival Approach with Lateral Skin Extension in Orbital Fracture Reconstruction: Poster Presentation - Case Series - Ophthalmologist - MIA NURSALAMAH; R. Angga Kartiwa; Ilman Fathony M. (Majalah Oftalmologi Indonesia, 2023)
Introduction : Orbital fractures are commonly featured in various type of facial fracture, including zygomaticomaxillary, naso-orbito-ethmoid, frontal-sinus, Le Fort II, and III fracture patterns. Multidisciplinary surgery is required to restore physiological and aesthetic functions. Case Illustration : Three midfacial fracture operations with lower transconjunctival incision approach to 6, 18, and 25 years old patients were performed by maxillofacial team in Al Islam Hospital Bandung. The steps started with lateral canthotomy and continued with transconjunctival incision in a lateromedial direction. With dissection towards the infraorbital rim, lower eyelid is mobilized and can be retracted anteromedially. Two patients was given titanium orbital floor implants and plates, while the youngest patient received absorbable plates. This approach successfully gave wider access to orbital bone and less bleeding during surgery. No complication has been reported with good outcome. Discussion : Fracture of the orbital floor may be repaired through transcutaneous, transconjunctival or endoscopic approaches. Transconjunctival approach is the most effective surgical access to infraorbital rim and orbital floor or even to medial orbital wall. The ability to reach periosteum further allows access to great portion of the orbit. Lateral canthotomy allows periosteum to be elevated superiorly for repair of fracture frontozygomatic suture. This approach may decrease the risk of postoperative eyelid retraction than subciliary approach and is aesthetically superior to other approaches. Conclusion : Transconjunctival approach has provided wider intraoperative access during orbital fracture reconstruction with easier post operative care, also giving good functional and aesthetic outcome.